2018
DOI: 10.1021/acs.est.8b02266
|View full text |Cite
|
Sign up to set email alerts
|

Is Sulfate Radical Really Generated from Peroxydisulfate Activated by Iron(II) for Environmental Decontamination?

Abstract: It is well documented that the traditional Fenton reagent (i.e., the combination of Fe(II) and HO) produces hydroxyl radical (OH) under acidic conditions, while at near-neutral pH the reactive intermediate converts to ferryl ion (Fe(IV)) that can oxidize sulfoxides to produce corresponding sulfones, markedly differing from their OH-induced products. However, it remains unclear whether Fe(IV) is generated in the Fe(II) activated peroxydisulfate (PDS) process, where sulfate radical (SO) is long recognized as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
306
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 618 publications
(322 citation statements)
references
References 56 publications
16
306
0
Order By: Relevance
“…This inference was supported byWang et al (2018) who found that DMPO • -OH adduct signal also occurred in DMPO trapped EPR spectra of Fe(II)/O 3 , Fe(II)/PDS, and Fe(II)/PMS systems, which were identified as Fe(IV)-dominated AOPs. Moreover, Zong et al (2021) also reported that • OH, formed by Fe(IV) self-decay, was responsible for DMPO • -OH adduct signal occurrence in the EPR spectra of Fe(II)/periodate system.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…This inference was supported byWang et al (2018) who found that DMPO • -OH adduct signal also occurred in DMPO trapped EPR spectra of Fe(II)/O 3 , Fe(II)/PDS, and Fe(II)/PMS systems, which were identified as Fe(IV)-dominated AOPs. Moreover, Zong et al (2021) also reported that • OH, formed by Fe(IV) self-decay, was responsible for DMPO • -OH adduct signal occurrence in the EPR spectra of Fe(II)/periodate system.…”
mentioning
confidence: 64%
“…1995 (Wang et al 2018, Wang et al 2019b, Wang et al 2019c, Wang et al 2020. In these studies, Wang et al firstly identified that Fe(IV) oxidized PMSO to methyl phenyl sulfone (PMSO 2 ) through oxygen-atom transfer, markedly different from the SO 4 •− and • OH involved oxidation products of PMSO (Wang et al 2018). Further, they observed that PMSO was almost completely transformed to PMSO 2 , the indicative of Fe(IV) formation, in Fe(II)/HSO 5 − (Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic iron center formed a highly oxidizing oxo-iron species Fe IV/V (namely, O = Fe IV and O = Fe V ) [65] which had the reaction with the sulfoxide in Scheme 5 to generate the corresponding sulfone by oxygen atom transfer step [61] , [62] . Formally, O = Fe V was best described as an oxo-Fe(IV)-porphyrin radical cation, namely, O = Fe IV (Por ) • + (O = Fe IV • + ) [65] , [66] .…”
Section: Resultsmentioning
confidence: 99%
“…ESR spectra of Fe(II) and thermally activated PPS was showed in Figure 7. The result showed that the intensity of the DMPO-SO 4 adduct signal was very weak, while the relatively strong DMPO-OH adduct signal appeared in the activated PPS system, but the free radicals were mainly sulfate radicals (Wang et al 2018b). The mechanism based on the persulfate oxidation system to improve sludge dewatering and disintegration performance was discussed by detecting the sludge extracellular polymeric substances (EPS) and Zeta potential, preliminarily determining the oxidation of target organic substances by activated persulfate (Guo et al 2019).…”
Section: Mechanism Analysis Of the Difference Between Thermally And Fe(ii) Activated Pps In Conditioning Sludgementioning
confidence: 98%